Correlation of axial length and corneal curvature with diopter in eyes of adults with anisometropia - Zeng, Jin (Int J Clin Exp Med, 2015)
Purpose: To analyze the causes of anisometropia. Methods: Between June 2011 and November 2012 101 participants were divided into three groups. The refraction comprising the degree of refractive errors in the presence of astigmatism which was converted into the degree of spherical equivalent as well as ocular axial length (AL), corneal curvature (CR), average corneal power (ave K) and diopters were measured. Results: The differences of ocular AL/CR and CR between two eyes were statistically significant among the three groups (P < 0.05). Standardized regression coefficients obtained by a multiple linear regression analysis indicated that AL/CR, AL and ave K differences correlated with anisometropia in descending order. Conclusion: The difference of AL/CR ratios between the eyes was the main cause for anisometropia, followed by AL and ave K values.